Merging a Negatively Curved Nanographene and a Carbon Nanoring - Yiqun Zhang; Daiyue Yang; Sai Ho Pun; Han Chen; Qian Miao (Precision Chemistry, 2023)
Two molecular nanocarbons result from merging a negatively curved nanographene and a carbon nanoring in two constitutional isomers of D2 and C2v symmetry, respectively. They were synthesized by attachment of C-shaped paraphenylene precursors to 2,11,18,27-tetrabromooctabenzo[8]circulene and the subsequent intramolecular Yamamoto coupling and reductive aromatization reactions. The flexible nature of octabenzo[8]circulene enabled two different ways of connection in the Yamamoto coupling reactions, leading to the two constitutional isomers. The D2 isomer is shaped like a figure eight, as revealed by X-ray crystallography, and is resolved into two enantiomers by chiral HPLC. The synthesis of the C2v isomer is regarded as a further step toward precision synthesis of carbon schwarzites through a bottom-up approach.